Security and devolution in Kenya: Struggles in applying constitutional provisions to local politics - Burbidge, D (Strathmore University Press, 2017)
The Fourth Schedule of the Constitution of Kenya (2010 Constitution) retains security as a function of National Government. At the same time, the 2010 Constitution creates 47 county governments with considerable autonomy in public service provision. Many county governors have demanded a say in the deployment of security services because of the inequality of security provision throughout Kenya’s history. While the 2010 Constitution is clear, however, in not providing much of a local say in the way security is deployed, it is found that in their day-to-day activities security officials depend on a close relationship with local politicians. This article examines constitutional provisions in the context of the history of security in Kenya and its practical deployment under the new political framework. It is argued that the long-term reasons for the inconsistent and insensitive use of security forces endure in contemporary dilemmas over the relationship between national security provision and local politics. Regardless of what the 2010 Constitution says, successful deployment of security depends on cooperative local political relations. Attempts to establish these links can often lead county governors to overstep their mandates, however, contravening the 2010 Constitution. We are therefore not only witnessing a transformation of the political structure through devolution but also transformation of the negotiated structure of security’s deployment.